Supporting consumer engagement in health research about chronic conditions: a scoping review of evidence-based resources - Mingming Zhou; Anne Parkinson; Mengyu Andy Lyu; Hanna Suominen; Leanne Watts; Jane Desborough (Research Involvement and Engagement)
Abstract Context and objective ‘Consumers’ refers to individuals with lived experience of health issues, as well as their carers or family members, who are often referred to as patients or service users. The recognition of consumers' expertise through lived experience is increasingly acknowledged as essential in health research design. Involving consumers in research enhances relevance and fosters high-quality, consumer-centric outcomes. While previous reviews have examined resources that support consumer engagement in health research, this review aimed to identify evidence-based resources specifically designed for engaging consumers in research related to chronic conditions. Design We conducted a scoping review to map diverse resources, using the Arksey and O'Malley framework, enhanced by Levac et al. and the Joanna Briggs Institute. Data collection A search strategy was developed using keywords related to consumer engagement and supporting resources, such as models, frameworks, and tools. Seven databases were searched: PubMed, Web of Science, Cochrane, Scopus, EconLit, PsycINFO, and ACM Digital Library, targeting peer-reviewed articles published between 2013 and 2023. Analysis We conducted a qualitative thematic analysis by coding the results sections of each included study line by line. The codes were inductively grouped into descriptive categories, which were then synthesised into analytical themes and sub-themes. Results From 15,245 identified articles, 15 met the inclusion criteria. An overarching framework for consumer engagement in health research related to chronic conditions was synthesised, comprising six themes: 1. Promoting reciprocal learning, 2. Fostering a supportive environment, 3. Providing training to build capacity, 4. Acknowledging consumer contributions, 5. Using resources to facilitate engagement, and 6. Evaluating engagement impact. Conclusion This review integrates existing evidence-based resources for supporting consumer engagement in research about chronic conditions and presents an overarching framework. The findings offer valuable guidance for researchers aiming to effectively implement consumer engagement strategies tailored to individuals with chronic conditions.